Regional climate engineering by radiation management: Prerequisites and prospects. Issue 12 (21st December 2016) - Quaas, Johannes; Quaas, Martin F.; Boucher, Olivier; Rickels, Wilfried
Abstract: Radiation management (RM), as an option to engineer the climate, is highly controversial and suffers from a number of ethical and regulatory concerns, usually studied in the context of the objective to mitigate the global mean temperature. In this article, we discuss the idea that RM can be differentiated and scaled in several dimensions with potential objectives being to influence a certain climate parameter in a specific region. Some short‐lived climate forcers (e.g., tropospheric aerosols) exhibit strong geographical and temporal variability, potentially leading to limited‐area climate responses. Marine cloud brightening and thinning or dissolution of cirrus clouds could be operated at a rather local scale. It is therefore conceivable that such schemes could be applied with the objective to influence the climate at a regional scale. From a governance perspective, it is desirable to avoid any substantial climate effects of regional RM outside the target region. This, however, could prove impossible for a sustained, long‐term RM. In turn, regional RM during limited time periods could prove more feasible without effects beyond the target area. It may be attractive as it potentially provides the opportunity to target the suppression of some extreme events such as heat waves. Research is needed on the traceability of regional RM, for example, using detection and attribution methods. Incentives and implications of regional RM need to be examined, and new governance options have to be conceived. Key Points: The article introduces the concept of regional radiation management and its prospects Regional‐scale economic incentives are demonstrated on the basis of published data Feasibility and traceability of regional climate modification need to be investigated and new governance options have to be conceived